Pelestarian Kesenian Tradisional Thek Thur Sanggar Ratua Masyarakat Dukuh Mirah Desa Nambangrejo Kecamatan Sukorejo Ponorogo - Toikun Toikun Toikun; Murdianto Murdianto; Syamsul Wathoni (Social Science Academic, 2025)
This article is entitled Preserving traditional art, namely Thek Thur of Sanggar Ratua, in the Dukuh Mirah community by holding a festival event. The Thek Thur Arts festival is a competition with a dichotomy of champion status and various symbols, which involves many agents in the contest. This research aims to know the meaning of the traditional contestation of the thek thur community of Dukuh Mirah and find out the effort is made to take part in the thur traditional art contest in Dukuh Mirah, Kecamatan Nambangrejo Village. The Nesearth method is a qualitative research method. The research location is at Thek Thur Sanggar Ratua Mirah Hamlet, Nambangrejo location is at Thek Thur Sanggar Ratua Mirah Hamlet, Nambangrejo Village, Sukorejo District, East Java. The research subjects were the Village, Sukorejo District, and East Java. The research subjects were the administrators and members of Thek Tur Sanggar Ratua. Supporting informants in this research are the government and art practitioners in Ponorogo Regency and the community as spectators and supporters of each studio—data collection techniques through observation, interviews, and documentation. Data validity techniques are carried out using data triangulation techniques. Data analysis techniques are carried out using data triangulation techniques. Data analysis techniques include data collection, reduction, presentation, and conclusion. Thek Thur Sanggar Ratua interprets Thek Thur Festival in Nambangrejo Village as a structure with all the rules, assessments, and awards to mark and obtain festival champion status. Intercity participation in the festival can be a milestone in the popularity of the Thur Sanggar Ratua Studio. Conversely, it becomes a rivalry between the two studios, which results in the dominance of champion status. The Thek Thur Sanggar Ratua Studio is present at the Thek Thur festival by forming a habitus, including routines for participating in the festival, obeying the festival rules, and training, as well as accumulating various capital, which indicates that the Thek Thur festival is an arena for the operational practices of the two studios of compete with each other so that they are able to accupy, maintain and change the status of campion.